Retrospective Review of Positive Newborn Screening Results for Isovaleric Acidemia and Development of a Strategy to Improve the Efficacy of Newborn Screening in the UK - Rachel S. Carling; Katy Hedgethorne; Anupam Chakrapani; Patricia L. Hall; Nick Flynn; Toby Greenfield; Stuart J. Moat; Joshua Ssali; Lynette Shakespeare; Nazia Taj; Teresa H. Y. Wu; Mark Anderson; et al. (MDPI AG, 2024)
Since the UK commenced newborn screening for isovaleric acidemia in 2015, changes in prescribing have increased the incidence of false positive (FP) results due to pivaloylcarnitine. A review of screening results between 2015 and 2022 identified 24 true positive (TP) and 84 FP cases, with pivalate interference confirmed in 76/84. Initial C5 carnitine (C5C) did not discriminate between FP and TP with median (range) C5C of 2.9 (2.0-9.6) and 4.0 (1.8->70) µmol/L, respectively, and neither did Precision Newborn Screening via Collaborative Laboratory Integrated Reports (CLIR), which identified only 1/47 FP cases. However, among the TP cases, disease severity showed a correlation with initial C5C in 'asymptomatic' individuals (n = 17), demonstrating a median (range) C5C of 3.0 (1.8-7.1) whilst 'clinically affected' patients (n = 7), showed a median (range) C5C of 13.9 (7.7-70) µmol/L. These findings allowed the introduction of dual cut-off values into the screening algorithm to reduce the incidence of FPs, with initial C5C results ≥ 5 µmol/L triggering urgent referral, and those >2.0 and <5.0 µmol/L prompting second-tier C5-isobar testing. This will avoid delayed referral in babies at particular risk whilst reducing the FP rate for the remainder.